1994
DOI: 10.1111/j.1432-1033.1994.tb19056.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of human serum amyloid P component (hSAP) to human neutrophils

Abstract: Human serum amyloid P component (hSAP) and human C-reactive protein (hCRP) are normal serum constituents related to the pentraxin family of plasma proteins. hSAP has morphological and immunochemical identity and extensive sequence similarity to the amyloid P (AP) component found in normal tissues and particularly in amyloid deposits. hCRP and its proteolytic products have been previously shown to bind and to interact with various types of human leukocytes. Binding-displacement experiments with '251-labeled hSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…SAP levels vary from ϳ20 -50 g/ml in normal individuals, with males having slightly higher levels than females (34). The binding of SAP to human PMN was previously demonstrated by Landsmann et al (13). These investigators reported that SAP bound to human PMN with high affinity and that CRP and SAP competed for binding.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…SAP levels vary from ϳ20 -50 g/ml in normal individuals, with males having slightly higher levels than females (34). The binding of SAP to human PMN was previously demonstrated by Landsmann et al (13). These investigators reported that SAP bound to human PMN with high affinity and that CRP and SAP competed for binding.…”
Section: Discussionmentioning
confidence: 84%
“…The existence of a receptor for SAP on mouse macrophages and human polymorphonuclear leukocytes (PMN) has been previously reported (12,13). However, the nature of the receptor and its function were unknown.…”
mentioning
confidence: 99%
“…We found previously that circulating Lselectin plasma concentrations drop by almost 50% in infants undergoing open heart surgery employing cardiopulmonary bypass [33], which may be due to trapping of soluble L-selectin by SAP absorbed onto the surface of plastic tubings. L-Selectin molecules are clustered at the tip of leukocyte microvilli [34] and are therefore candidates to explain the binding of SAP observed in leukocytes [35]. Indeed, in a fashion analogous to GlyCAM-1 [14], SAP elicited rapid activation of b2 integrins on human lymphocytes, as assessed by expression of the mAb 24-recognized neoepitope.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that SAP can interact with phagocytes via specific receptors (19,29). Furthermore, the ability of substrate-bound SAP to activate C3b and C3bi receptors of monocytes has been described (29).…”
Section: Discussionmentioning
confidence: 99%